If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 9 + n Solving -4 = 9 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -4 + -1n = 9 + n + -1n Combine like terms: n + -1n = 0 -4 + -1n = 9 + 0 -4 + -1n = 9 Add '4' to each side of the equation. -4 + 4 + -1n = 9 + 4 Combine like terms: -4 + 4 = 0 0 + -1n = 9 + 4 -1n = 9 + 4 Combine like terms: 9 + 4 = 13 -1n = 13 Divide each side by '-1'. n = -13 Simplifying n = -13
| 6k^2+3k-18=0 | | 3x^2-60x+298=0 | | v=w(w+3)(2w) | | 2h+5=75 | | 2x^2-4=-5x | | 3.2-0.04= | | y/5-0.4=0.33-y | | 3x/7y | | .1070=x+(x-.056)(1.1)(1-.35) | | 10.70=x+(x-.056)(1.1)(1-.35) | | 5x-8=6-2 | | -12=x/5 | | 12=6+6(x-11) | | 4+3(2x-1)=19 | | 8x-3x+6x-x=5-14+6+3 | | 6/8x=9 | | .25x-0.08=.167x+.167 | | 0.5x^2-0.25x+0.1= | | 9x-9-7x=-x+6 | | Y=0.5x^2-0.25x+0.1 | | 8x-14-3x-6+6x-x=5-14+6+3 | | 2x-3.33=6-0.33x | | 9x-9-7x=-x+x | | x-3x-5=35 | | 18=x^2-x-2 | | x^2+6x-33=0 | | 6-2(3-2x)+6=32 | | 19=8+k | | 38=2L+2(4) | | .25x-1=.5x+1.5 | | (3+z)(3z-8)=0 | | 6x-36/x^2-6x |